2023
DOI: 10.1021/acs.organomet.3c00064
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Ruthenium Catalyst for Effective Renewable Hydrogen Production from Biomass-Derived Sorbitol

Abstract: In the present worldwide situation, the transition to a more sustainable hydrogen economy from the prevailing energy infrastructure is gaining great attention. Herein, for hydrogen production from biomass-derived sorbitol, we employed a bifunctional NNN−Ru system bearing protic arms in a ligand scaffold liable for a metal−ligand cooperativity pathway as well as a secondary-coordination-sphere hydrogen-bonding interaction for the appropriate substrate orientation at the active center. A maximum turnover number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Ethylene glycol (EG) is considered the simplest and most abundant vicinal diol, having high hydrogen storage capacity (6.5 wt%). 52 a The generation of hydrogen from ethylene glycol, a flexible and easily accessible molecule, has gained a lot of interest recently as a potential source of sustainable energy and has been studied using both heterogeneous 52 b – l and homogeneous 47,54–58 catalysts. In this section, we will delve into the fascinating world of hydrogen generation from ethylene glycol using pincer catalysts, involving novel approaches and discussing the possible mechanism involved in such transformations.…”
Section: Hydrogen Production From Alcoholsmentioning
confidence: 99%
“…Ethylene glycol (EG) is considered the simplest and most abundant vicinal diol, having high hydrogen storage capacity (6.5 wt%). 52 a The generation of hydrogen from ethylene glycol, a flexible and easily accessible molecule, has gained a lot of interest recently as a potential source of sustainable energy and has been studied using both heterogeneous 52 b – l and homogeneous 47,54–58 catalysts. In this section, we will delve into the fascinating world of hydrogen generation from ethylene glycol using pincer catalysts, involving novel approaches and discussing the possible mechanism involved in such transformations.…”
Section: Hydrogen Production From Alcoholsmentioning
confidence: 99%
“…In our previous report, the catalytic performance of complex 1 (Scheme 1b) was explored for the generation of hydrogen from biomass-derived sorbitol, where the mechanistic studies revealed the fine-tuning of ligand architecture had a pivotal influence on the catalytic activity and facilitated the cooperative mechanism. 30 To bring the development forward to the path of being put into effort here, we attempt to produce selectively green hydrogen from ethylene glycol under two different operating conditions. The first optimized strategy operates under relatively mild reaction conditions, leading to the selective production of glycolic acid with the evolution of pure hydrogen at a high initial rate.…”
mentioning
confidence: 99%
“…of NEt 3 , and the formation of 1a was observed as reported earlier (Scheme S1†). 30 In the same reaction, the addition of glyoxal (10 equiv.) resulted in a peak at 42.03 ppm in 31 P NMR, probably due to the interaction of glyoxal, followed by the addition of KOH (2.5 equiv.…”
mentioning
confidence: 99%
See 1 more Smart Citation